2012
DOI: 10.1002/smll.201102736
|View full text |Cite
|
Sign up to set email alerts
|

High‐Sensitivity Fluorescence Lifetime Thermal Sensing Based on CdTe Quantum Dots

Abstract: The potential use of CdTe quantum dots as luminescence nano-probes for lifetime fluorescence nano-thermometry is demonstrated. The maximum thermal sensitivity achievable is strongly dependent on the quantum dot size. For the smallest sizes (close to 1 nm) the lifetime thermal sensitivity overcomes those of conventional nano-probes used in fluorescence lifetime thermometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
75
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(85 citation statements)
references
References 45 publications
5
75
0
Order By: Relevance
“…The observed size dependence of the PL lifetime is in good agreement with previous reports on PL decay dynamics of CdTe QDs dispersed in colloidal solution. [ 36,60 ] The decrease of QD size implies an increase of the surface-tovolume ratio and accordingly nonradiative decay rate ( nr 1 τ − ) through the trap-related states. At the same time, a monotonic increase of the radiative decay rate ( 1 r τ − ) is predicted as the emission frequency increases (i.e., as the QD size decreases), [ 61 ] in accord with experimental observations [ 62 ] and as predicted by Fermi's Golden Rule.…”
Section: Time-resolved Plmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed size dependence of the PL lifetime is in good agreement with previous reports on PL decay dynamics of CdTe QDs dispersed in colloidal solution. [ 36,60 ] The decrease of QD size implies an increase of the surface-tovolume ratio and accordingly nonradiative decay rate ( nr 1 τ − ) through the trap-related states. At the same time, a monotonic increase of the radiative decay rate ( 1 r τ − ) is predicted as the emission frequency increases (i.e., as the QD size decreases), [ 61 ] in accord with experimental observations [ 62 ] and as predicted by Fermi's Golden Rule.…”
Section: Time-resolved Plmentioning
confidence: 99%
“…Additionally, this method is not affected by light scattering, refl ection, or intensity fl uctuations of the excitation source. [ 9,36 ] The CdTe QDs@NaCl powder ( d QDs = 2.3 nm) provides a thermal reading over a wide temperature range. In the previous studies, thermal sensing was achieved by monitoring the PL lifetime change of the main PL peak (excitonic).…”
Section: Pl Lifetime Thermal Sensingmentioning
confidence: 99%
“…The lifetime-based techniques generally require more complex diagnostic equipment compared to intensity-based measurements, though they are less sensitive to environmental effects. Besides the temperature measurements, the fluorescent techniques also were employed in studies of flows inside micro channels in lab-on-chip applications [9,10], in microviscosity investigations [11,12], air flow sensing [13,14], and as pressure measurements [15]. In order to achieve stable and reliable results, the certain balance between isolation and overlap of the probe with the environment is desired.…”
Section: Introductionmentioning
confidence: 99%
“…294,295 Jaque's group has investigated this phenomenon for thermometry applications and found that optimum temperature sensitivity can be obtained with smaller sized QDs and the use of CdTe over CdSe. 296 Spectral shifts are accompanied by changes in PL lifetime where, for example, CdTe QD 515 (1 nm in diameter) exhibited a thermal sensitivity of -0.017 8C -1 (measured as the relative change in lifetime per degree Celsius) between 27 and 50 8C. This sensitivity was comparable to rhodamine B-doped microspheres (0.0016 8C -1 ) and Kiton red dye (0.011 8C -1 ), 296 suggesting that QDs might be useful probes for FLIM-based measurement of intracellular temperature.…”
mentioning
confidence: 99%
“…296 Spectral shifts are accompanied by changes in PL lifetime where, for example, CdTe QD 515 (1 nm in diameter) exhibited a thermal sensitivity of -0.017 8C -1 (measured as the relative change in lifetime per degree Celsius) between 27 and 50 8C. This sensitivity was comparable to rhodamine B-doped microspheres (0.0016 8C -1 ) and Kiton red dye (0.011 8C -1 ), 296 suggesting that QDs might be useful probes for FLIM-based measurement of intracellular temperature. Such measurements are important for identifying ''hot'' malignant cells (higher metabolic activity compared with healthy cells) and monitoring hyperthermic treatment of those cells.…”
mentioning
confidence: 99%